Development of Part and Whole Learning of Swimming Materials in Swimming Extracurricular at SMA Negeri 1 Tumpang - Vania Putri Hariyoko; Ari Wibowo Kurniawan; Usman Wahyudi (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
The process of learning basic techniques and swimming styles is the first very important thing that students must have in the swimming extracurricular at SMA Negeri 1 Tumpang. In extracurricular swimming there are still no manuals that can be used to support student learning. The implementation of extracurricular swimming is still very lacking because implementation is uncertain every week. Based on the results of observations, it shows that 93.3% of SMA Negeri 1 Tumpang students need books as a guide to basic swimming learning techniques. The aim is to develop part and whole swimming learning in extracurricular swimming at SMA Negeri 1 Tumpang by providing assistance in the form of ebooks to students so that they have a guidebook on basic swimming techniques. This research is Research and Development (R&D) research using the Borg and Gall development model. With initial field trial subjects of 6 students and large field trials of 30 students. Based on data obtained from the results of data analysis from experts, namely media experts, 98% results were obtained from learning experts, 95% results were obtained from swimming experts, 98% results were obtained from initial field trials, initial field trials obtained 97% results and large field trials obtained 96% results. The results of data analysis from experts and field trials obtained the result